Spin resonance and spin fluctuations in a quantum wire - Pokrovsky, V.L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
This is a review of theoretical works on spin resonance in a quantum wire associated with the spin-orbit interaction. We demonstrate that the spin-orbit induced internal “magnetic field” leads to a narrow spin-flip resonance at low temperatures in the absence of an applied magnetic field. An applied dc magnetic field perpendicular to and small compared with the spin-orbit field enhances the resonance absorption by several orders of magnitude. The component of applied field parallel to the spin-orbit field separates the resonance frequencies of right and left movers and enables a linearly polarized ac electric field to produce a dynamic magnetization as well as electric and spin currents. We start with a simple model of noninteracting electrons and then consider the interaction that is not weak in 1d electron system. We show that electron spin resonance in the spin-orbit field persists in the Luttinger liquid. The interaction produces an additional singularity (cusp) in the spin-flip channel associated with the plasma oscillation. As it was shown earlier by Starykh and his coworkers, the interacting 1d electron system in the external field with sufficiently large parallel component becomes unstable with respect to the appearance of a spin-density wave. This instability suppresses the spin resonance. The observation of the electron spin resonance in a thin wires requires low temperature and high intensity of electromagnetic field in the teraherz diapason. The experiment satisfying these two requirements is possible but rather difficult. An alternative approach that does not require strong ac field is to study two-time correlations of the total spin of the wire with an optical method developed by S.A. Crooker and coworkers. We developed theory of such correlations. We prove that the correlation of the total spin component parallel to the internal magnetic field is dominant in systems with the developed spin-density waves but it vanishes in Luttinger liquid. Thus, the measurement of spin correlations is a diagnostic tool to distinguish between the two states of electronic liquid in the quantum wire.